Standardized Chromosome Pattern of Some Amphibians in Phetchabun Province - Aiumsumang, Surachest; Khoomsab, Kan; Tangsuwan, Itsara; Phimphan, Sumalee (KKU Science Journal, 2023)
This research aimed to examine standardized chromosome pattern of some amphibians in Phetchabun Province, including Kaloula pulchra, Polypedates leucomystax and Fejervarya limnocharis. The samples were collected from Phetchabun Province, Thailand. The bone marrow cells from each male and female individual were gently minced using direct method for metaphase chromosome preparation. The conventional staining by Giemsa’s were applied to stain the chromosomes. The results showed that the Kaloula pulchra was the number of diploid chromosome (2n) = 28 and fundamental number was 56 in both male and female. The karyotype of Kaloula pulchra comprised of 8 metacentric and 18 submetacentric chromosomes. The karyotype formula is as follows: 2n (28) = 8m + 18sm. The Polypedates leucomystax was 2n = 26 and NF = 52 in both male and female. The karyotype of P. leucomystax comprised of 20 metacentric and 6 submetacentric chromosomes. The karyotype formula is as follows: 2n (26) = 20m + 6sm. The Fejervarya limnocharis had 2n = 26 and NF = 52 in both male and female. The karyotype of F. limnocharis comprised of 14 metacentric, 10 submetacentric and 2 acrocentric chromosomes. The karyotype formula is as follows: 2n (26) = 14m + 10sm + 2a.